CCl4-induced hepatotoxicity: protective effect of rutin on p53, CYP2E1 and the antioxidative status in rat - Khan Rahmat A; Khan Muhammad R; Sahreen Sumaira (BMC Complementary and Alternative Medicine, 2012)
Abstract Background Rutin is a polyphenolic natural flavonoid which possesses antioxidant and anticancer activity. In the present study the hepatoprotective effect of rutin was evaluated against carbon tetrachloride (CCl4)-induced liver injuries in rats. Methods and materials 24 Sprague–Dawley male rats were equally divided into 4 groups for the assessment of hepatoprotective potential of rutin. Rats of group I (control) received only vehicles; 1 ml/kg bw of saline (0.85%) and olive oil (3 ml/kg) and had free access to food and water. Rats of group II, III and IV were treated with CCl4 (30% in olive oil, 3 ml/kg bw) via the intraperitoneal route twice a week for four weeks. The rutin at the doses of 50 and 70 mg/kg were administered intragastrically after 48 h of CCl4 treatment to group III and IV, respectively. Protective effect of rutin on serum enzyme level, lipid profile, activities of antioxidant enzymes and molecular markers were calculated in CCl4-induced hepatotoxicity in rat. Results Rutin showed significant protection with the depletion of alanine aminotransferase (ALT), aspartate aminotransferase (AST), alkaline phosphatase (ALP), gamma glutamyl transpeptidase (γ-GT) in serum as was raised by the induction of CCl4. Concentration of serum triglycerides, total cholesterol and low density lipoproteins was increased while high-density lipoprotein was decreased with rutin in a dose dependent manner. Activity level of endogenous liver antioxidant enzymes; catalase (CAT), superoxide dismutase (SOD), glutathione peroxidase (GSHpx), glutathione-S-transferase (GST) and glutathione reductase (GSR) and glutathione (GSH) contents were increased while lipid peroxidation (TBARS) was decreased dose dependently with rutin. Moreover, increase in DNA fragmentation and oxo8dG damages while decrease in p53 and CYP 2E1 expression induced with CCl4 was restored with the treatment of rutin. Conclusion From these results, it is suggested that rutin possesses hepatoprotective properties.